2021
DOI: 10.1186/s12978-021-01221-9
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perspectives on the measures that need to be taken to increase the use of health-care facility delivery service among slums women, Addis Ababa, Ethiopia: a qualitative study

Abstract: Background Global strategies to target high maternal mortality ratios are focused on providing skilled attendance at delivery along with access to emergency obstetric care. Research that examines strategies to increase facility-based skilled birth attendance among slum residents in Addis Ababa, Ethiopia, is limited. Objective The study aimed to explore women's perspectives on the measures that need to be taken to increase the use of the facility—de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Home remedy and home management delayed healthcare-seeking behaviour 52 70 81 84. In addition, perception,21 42 63 75 83 85–89 knowledge21 42 48 60 67 74 81 85 90–95 and experience of healthcare services39 49 59 61 66 69 74 79 86 96 97 including fear and distrust of healthcare services,21 38 67 71 74 75 78 88 98–100 and preference related to care provider’s gender87 101 were frequently cited factors. Provider shopping associated with distrust of healthcare providers and denial of diagnosis delayed first care seeking and treatment initiation of patients with pulmonary tuberculosis in India 70.…”
Section: Resultsmentioning
confidence: 99%
“…Home remedy and home management delayed healthcare-seeking behaviour 52 70 81 84. In addition, perception,21 42 63 75 83 85–89 knowledge21 42 48 60 67 74 81 85 90–95 and experience of healthcare services39 49 59 61 66 69 74 79 86 96 97 including fear and distrust of healthcare services,21 38 67 71 74 75 78 88 98–100 and preference related to care provider’s gender87 101 were frequently cited factors. Provider shopping associated with distrust of healthcare providers and denial of diagnosis delayed first care seeking and treatment initiation of patients with pulmonary tuberculosis in India 70.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] A community-based study in Ethiopia reported physical abuse of 23.2%,[ 21 ] higher than ours. However, other studies in the same country reported only 2% to 2.3% of physical or verbal abuse[ 1 22 ]; in some African studies, poor reporting could be because of a lack of awareness or perceived normalization of abuse. [ 9 ] In the present study, women reported 70.55% continuity of care, similar to study findings in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…However, 94.30% of our study participants reported non-confidential care, higher than those conducted in Addis Ababa, Ethiopia (16.3%). [ 1 ] The discrepancy may be due to faulty perception of women, poor communication of HCWs with women, overburden at work, insufficient space in the labor room, and shortage of HCWs. Women reported 9.45% non-dignified care in our study and 23.77% abandonment and denial of care, which was higher when compared to other studies in India[ 16 17 ] and abroad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation